2023
DOI: 10.3389/fonc.2023.1104262
|View full text |Cite|
|
Sign up to set email alerts
|

Single-cell transcriptome analysis reveals the metabolic changes and the prognostic value of malignant hepatocyte subpopulations and predict new therapeutic agents for hepatocellular carcinoma

Abstract: BackgroundThe development of HCC is often associated with extensive metabolic disturbances. Single cell RNA sequencing (scRNA-seq) provides a better understanding of cellular behavior in the context of complex tumor microenvironments by analyzing individual cell populations. MethodsThe Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) data was employed to investigate the metabolic pathways in HCC. Principal component analysis (PCA) and uniform manifold approximation and projection (UMAP) analysis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Previously reported qPCR analyses showed that MARCKSL1 , PAGE1 , and UCK2 were upregulated in HCC cells. 2224 We found that these genes were more highly expressed in Huh7 than in LO2 cells. This discovery was consistent with earlier reports.…”
Section: Resultsmentioning
confidence: 77%
“…Previously reported qPCR analyses showed that MARCKSL1 , PAGE1 , and UCK2 were upregulated in HCC cells. 2224 We found that these genes were more highly expressed in Huh7 than in LO2 cells. This discovery was consistent with earlier reports.…”
Section: Resultsmentioning
confidence: 77%